Effect of Plant Growth-Promoting Rhizobacteria Synthetic Consortium on Growth, Yield, and Metabolic Profile of Lettuce (Lactuca sativa L.) Grown Under Suboptimal Nutrient Regime - Renée Abou Jaoudé; Francesca Luziatelli; Anna Grazia Ficca; Maurizio Ruzzi (Horticulturae)
Soilless cultivation allows for the exploitation of the benefits of plant growth-promoting rhizobacteria (PGPR) without the loss of efficacy observed with soil inoculation. In this study, we investigated the effects of a PGPR consortium on the plant growth, ecophysiology, and metabolic profile of lettuce (Lactuca sativa L.) grown in an aeroponic system under a low-nutrient regime. Overall, the plant biomass increased by 25% in the PGPR-inoculated plants due to enhanced leaf and root growth. The rise in the leaf biomass was primarily due to an increase in the leaf number and average leaf mass, coupled with a higher total leaf area. In addition, the inoculated plants exhibited an altered leaf anatomy characterized by an increased palisade parenchyma thickness and reduced airspace area, suggesting an improved photosynthetic efficiency and changes in the mesophyll conductance. The root morphology was also altered, with the PGPR-inoculated plants showing higher lateral root development. Furthermore, PGPR inoculation induced significant metabolic reprogramming in the leaves, affecting several pathways related to growth, development, and stress responses. These findings provide valuable insights into the intricate metabolic dialog between plants and beneficial microbes and demonstrate that the integration of soilless culture with an analysis of the ecophysiological, anatomical, and metabolomic plant responses can be a powerful approach to accelerate the design of new PGPR consortia for use as microbial biostimulants.